Searching for optimal parameters while developing CAD system for stellarator magnetic traps - Vorobyova, V.P.; Lukyanova, V.P.; Martynov, S.A.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2004)
This article is about development of mathematical model, algorithms and software for determining optimal parameters of magnetic field of toroidal stellarator magnetic systems.